Ответ:
(0;8)
Объяснение:
АС=ВС
С(0;у)
[tex]ac = \sqrt{ {(0 - 3)}^{2} + {(y - 1)}^{2} } [/tex]
[tex]bc = \sqrt{ {(0 - 7)}^{2} + {(y - 5)}^{2} } [/tex]
[tex] \sqrt{ {3}^{2} + {(y - 1)}^{2} } = \sqrt{ {7}^{2} + {(y - 5)}^{2} } \\ 9 + {y }^{2} - 2y + 1 = 49 + {y}^{2} - 10y + 25 \\ {y }^{2} - 2y - {y}^{2} + 10y = 49 + 25 - 9 - 1 \\ 8y = 64 \\ y = 64 \div 8 \\ y = 8[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(0;8)
Объяснение:
АС=ВС
С(0;у)
[tex]ac = \sqrt{ {(0 - 3)}^{2} + {(y - 1)}^{2} } [/tex]
[tex]bc = \sqrt{ {(0 - 7)}^{2} + {(y - 5)}^{2} } [/tex]
[tex] \sqrt{ {3}^{2} + {(y - 1)}^{2} } = \sqrt{ {7}^{2} + {(y - 5)}^{2} } \\ 9 + {y }^{2} - 2y + 1 = 49 + {y}^{2} - 10y + 25 \\ {y }^{2} - 2y - {y}^{2} + 10y = 49 + 25 - 9 - 1 \\ 8y = 64 \\ y = 64 \div 8 \\ y = 8[/tex]